Validation of an Integrated IS Success Model in the Study of E-Government - Waleed Mugahed Al-Rahmi (9451833) (2022)
Electronic government (E-government) systems are becoming an integral component of government service delivery systems. Because of the rapid growth of Internet and Information System (IS) technologies in Malaysia, E-government systems are becoming more and more necessary. This study examined user attitudes, usage intensions, and satisfaction with E-government systems using the Information System (IS) success model and the Technology Acceptance Model (TAM). This study deployed a questionnaire to 714 E-government users. The questionnaire results were analysed using the structural equation model (SEM). This study found that E-government perceived ease of use and perceived usefulness were strongly influenced by IS success model constructs and perceived trust. This study also found that user attitudes, usage intensions, and satisfaction were strongly influenced by TAM factors. Other Information Published in: Mobile Information Systems License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1155/2022/8909724 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.